Imprensa literária e modernidade: o naturalismo no periódico A Quinzena (1887-1888) - Gabriela Ramos Souza (2016)
Driven by a modern ideal of progress and development through the construction of the Brazilian nation and the civilization from the Brazilian state of Ceará through the propagation of literature as well as other arts and sciences, the Literary Club society (Clube Literário, 1886) produced 30 editions of the publication A Quinzena, which was created by a group of intelectuals who were part of Cearás literary scene. The bimonthly was promoted between 1887-1888, becoming the first publication from the provinces literary press to have been produced by a writers society. In its pages, the periodical presents the point of view of authors outside the royal courts circuit, which excluded the diverse manifestations spreadacross the country, showing another side of societys absorption of modernity. Despite remaining outside this nucleus, intelectuals from the then-province of Ceará maintained very intense cultural lives and activities, second only to Rio de Janeiro in their search for integration to the national project that was the construction of a Brazilian literature. Heirs to the 1870 generation and involved with the abolitionist campaign that resulted in the liberation of Cearás captives in 1884, members of the Literary Club came from the political newspaper Libertador. United in pursuit of promoting literature, they aimed to create a readership fortheir productions. For that reason the publication gathered intelectuals from various fields of knowledge, but especially the work of writers Oliveira Paiva, Rodolfo Teófilo, Juvenal Galeno and Antônio Sales. At least one poem, short story and literary critique were published in every issue. Through the panorama of the provinces historical context and manifestations of the literary culture, we observe the birth of A Quinzena as related to the formation of a local literary press, influenced by the national experience. The analysis of the bimonthly publication identifies frequent themes and approaches as well as theoretical influences andaesthetic tendencies absorbed by the writers, who aimed to promote the periods most current thinking in order to be involved with the modern debates taking place in Rio de Janeiro and in Europe. Therefore, we identify themes related to the natural sciences and naturalistic literatureas the most recurrent, the last one developed mainly in critical literary essays. With the analysis of writer Oliveira Paivas production of essays and short stories in the publication, we identify a defense of a naturalistic aesthetic, understood by members of the group as the path to the construction of Brazilian literature. We identify, therefore, points of contact between the writers individual project and the clubs collective project, related to modern national demands that would go on to reverberate years later in Brazil across literature, and in many other knowledge areas.